Study Of Factors Affecting The Thermal Conductivity Of Iraqi Bentonite (Baghdad Science Journal, 2012)
Thermal conductivity of compacted bentonite is one of the most important properties where this type of clay is proposed for use as a buffer material. In this study, Lee's disc method was used to measure the thermal conductivity of compacted bentonite specimens. The experimental results have been analyzed to observe the three major factors affecting the thermal conductivity of bentonite buffer material. While the clay density reaches to a target value, the measurement is taken to evaluate the thermal conductivity. By repeating this procedure, a relationship between clay dry density and thermal conductivity has been established in specimens after adjusting the water contents of the bentonite by placing its specimens in a drying oven for different periods. So relationships of thermal conductivity with each of these major factors (clay density, water content, and sand volume fraction) are established in this study. The relevance of these relationships be analyzed together using experimental data on many compacted bentonites.